Village Government Financial Performance Analysis in Fiscal Year 2022-2024 (Case Study in Independent Village in Muara Bulian District) - Novrianti, Ning Intan; Sam, Iskandar; Ridwan, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to evaluate the financial performance of the Independent Village Government in Muara Bulian District for the 2022-2024. The analysis focuses on key aspects of village financial management, such as budget planning, budget execution, and financial accountability. A descriptive quantitative approach is applied in this study. The findings suggest that the Independent Village Government in Muara Bulian District has managed village finances fairly well, despite facing challenges related to efficiency and transparency in budget usage. Several programs funded by the APBDesa have been successfully executed; however, there is still room for improvement in managing village assets and overseeing budget usage. Based on these results, the study recommends enhancing the capacity of village officials in financial management and strengthening the internal monitoring system to ensure more effective and targeted use of the budget.